Type 2 leprosy reaction with Sweet's syndrome-like presentation - Francielle Chiavelli Chiaratti; Egon Luiz Rodrigues Daxbacher; Antonielle Borges Faria Neumann; Thiago Jeunon (Sociedade Brasileira de Dermatologia, 2016)
Abstract Leprosy is a chronic disease characterized by manifestations in the peripheral nerves and skin. The course of the disease may be interrupted by acute phenomena called reactions. This article reports a peculiar case of type 2 leprosy reaction with Sweet's syndrome-like features as the first clinical manifestation of leprosy, resulting in a delay in the diagnosis due to unusual clinical presentation. The patient had clinical and histopathological features reminiscent of Sweet's syndrome associated with clusters of vacuolated histiocytes containing acid-fast bacilli isolated or forming globi. Herein, it is discussed how to recognize type 2 leprosy reaction with Sweet's syndrome features, the differential diagnosis with type 1 leprosy reaction and the treatment options. When this kind of reaction is the first clinical presentation of leprosy, the correct diagnosis might be not suspected clinically, and established only with histopathologic evaluation.